Effect of antioxidant and mustard oil emulsion on post harvest shelf life of fresh fruits of date palm cv. Barhee (Indian Journal of Arid Horticulture, 2025)
Date palm (Phoenix dectylifera L.) is a highly nutritious fruit crop. It is usually eaten as fresh (fruits harvested at khalal stage) and fully ripened fruit (harvested at pind or tamer stage). Date is highly nutritious fruit. Besides carbohydrate and protein, date fruit provides small amount of copper, magnesium, chlorine, sulphur, Vit A, B, and B, The following contents are an average for all date varieties at khalal stage: moisture 59.2%, nitrogen 1.2%, fat 0.4%, carbohydrate 33.8%, energy 144 calories/kg, calcium 22 mg/100g, and phosphorus 38 mg/100gm.
Keywords: harvest; magnesium